Demand-led growth and accommodating supply - Steven Fazzari; Piero Ferri; AnnaMaria Variato (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2018)
This paper presents a "supermultiplier" model in which the growth of autonomous demand (demand independent of the state of the economy) determines the steady-state growth rate of output. With reasonable parameters, endogenous adjustment of labor supply and productivity causes supply to accommodate the demand-led growth path, reconciling Harrod's warranted rate of demand growth with the growth of supply. The model delivers a range of feasible aggregate growth paths and unemployment rates rather than a single "natural rate." The results explain how economies can become trapped with low growth due to weak demand or fiscal austerity and suggest policy responses to "secular stagnation."
Keywords: E12; O40; E32; 330; demand-led growth; autonomous demand; supermultiplier; aggregate demand and supply reconciliation; secular stagnation